On Different Perspective: Image of Yogyakarta as a Tourist Destination from Domestic and International Tourist’s Perception - Maizida, Karlina (E-Journal of Tourism; Volume 8 Number 1 (March 2021), 2021)
This study examines the differences in how domestic and international tourists perceived the image of Yogyakarta as a tourist destination. This survey-based quantitative research used online-questionnaire to collect data from the domestic and international tourists who have visited Yogyakarta. Using a non-probability convenience sampling method, 304 useable questionnaire responses were collected through any social media network. The image of Yogyakarta as a tourist destination in this study consists of four parts: top of mind image, destination visual image selection, cognitive and affective evaluation. To test the different perspectives about cognitive and affective components of an image between domestic and international tourists, a non-parametric Mann-Whitney u-test was performed. The result shows that there is a significant difference in cognitive evaluation about an image of Yogyakarta as a destination nevertheless, no significant difference was found in the affective evaluation. The differences also appeared in the part of visual image selection whereas domestic tourists mostly choose Malioboro as the best picture to describe Yogyakarta while international tourists choose a Temple more than others. At the top-of-mind, international tourists mentioned Borobudur as a part of heritage sites and history frequently while most domestic tourists mentioned art and culture, shopping, and culinary. Furthermore, a methodological issue and practical implication are also discussed.